INFLUENCE OF IMPLEMENTING GOOD GOVERNANCE PRINCIPLES REGARDING THE EFFICACY OF EMPLOYEE PERFORMANCE - Rina Maulina; Suria Ningsih (Kajian Akuntansi, 2023)
The objective of the study was to ascertain whether application of Good Governance Principles would have an impact on the effective performance of government staff in Agriculture and Food Crops and Horticulture, West Aceh Regency. In this study, a statistical method is used to process the quantitative data. A statistical method based on the processing of quantitative data is used in this study. This study uses primary data sources, namely a number of written observations submitted to the research sample comprising 41 staff members from the Department of agriculture, Food Crops & Horticulture in West Aceh by distributing questionnaires. Simple linear regression is used as a data analysis tool. The results of this study have shown that applying good governance principles can significantly impact on the effectiveness of staff performance. Keywords: Good Governance, Effectiveness Employee Performance.